Rituximab-combined anthracycline-free chemotherapy in newly diagnosed paediatric and adolescent patients with non-high-risk aggressive mature B cell lymphoma: protocol for a single-arm, open-label, multicentre, phase II study (the Japan Children’s Cancer Group Multicentre Trial, JPLSG B-NHL-20) - Hiroya Hashimoto; Masahiro Sekimizu; Tetsuya Mori; Naoto Fujita; Reiji Fukano; Yuhki Koga; Tetsuo Mitsui; Takeshi Mori; Daiki Hori; Makito Tanaka; Kentaro Ohki; Hideto Iwafuchi; et al. (BMJ Open)
Introduction Children and adolescents with mature B cell non-Hodgkin lymphoma (B-NHL) are treated with short-intensive chemotherapy. The burden of short-term and long-term toxicity is highly relative to its high cure rate in good-risk patients. Although the addition of rituximab to standard lymphome Malin B (LMB) chemotherapy markedly prolongs event-free survival and overall survival in high-risk patients, the benefit of rituximab in good-risk patients remains to be elucidated. This clinical trial will examine whether the addition of rituximab eliminates anthracyclines in good-risk patients without compromising treatment outcomes.Methods and analysis We will perform a single-arm, open-label, multicentre phase II study. Low-risk (stage I – completely resected, stage II abdominal) and intermediate-risk (stages I and II – incompletely resected; stage II – resected, other than abdominal; stage III with LDH <2× upper limit of normal) patients with newly diagnosed B-NHL are eligible. Low-risk patients receive two courses of R-COM1P (rituximab, cyclophosphamide, vincristine, methotrexate, prednisolone and intrathecal methotrexate with hydrocortisone), and intermediate-risk patients receive COP (cyclophosphamide, vincristine, prednisolone and intrathecal methotrexate with hydrocortisone) followed by two courses each of R-COM3P and R-CYM (rituximab, cytarabine, methotrexate and intrathecal methotrexate with hydrocortisone). The primary endpoint is a 3-year event-free survival rate in paediatric patients (<18 years) with intermediate-risk disease. 100 patients (10 low-risk and 90 intermediate-risk) will enrol within a 4-year enrolment period and the follow-up period will be 3 years. 108 institutions are participating as of 1 January 2024 (64 university hospitals, 29 general hospitals, 12 children’s hospitals and three cancer centres).Ethics and dissemination This research was approved by the Certified Review Board at NHO Nagoya Medical Center (Nagoya, Japan) on 21 September 2021. Written informed consent is obtained from all patients and/or their guardians. The results of this study will be disseminated through peer-reviewed publications and conference presentations.Study registration Japan Registry of Clinical Trials, jRCTs041210104.